L2-induced gain for discrete-time switched Lur'e systems via a suitable Lyapunov function. Issue 25 (2015) - Louis, Julien; Jungers, Marc; Daafouz, Jamal; Castelan, Eugênio B.
Abstract: This paper deals with discrete-time switched Lur'e systems including an additional saturated input and a bounded energy disturbance. Two control design issues are investigated related to the L 2 -induced gain and the rejection of disturbance. An common optimization problem under LMI conditions and differing from the cost function to optimize, is provided to offer a solution to the both problems. The main approach is to upper bound a criterion with a suitable Lur'e type Lyapunov function. Numerical examples are given to underline the efficiency of our approach and to allow a discussion with the literature.